Pendapatan dan Sikap Wanita Tani dalam Bercocok Tanam Sayuran Sawi di Kelurahan Anawai Kecamatan Wua-Wua Kota Kendari - Elisabeth Yanti Pasarang; Dasmin Sidu; Mardin Mardin (Fakultas Pertanian Universitas Halu Oleo, 2022)
This research aimed to: (1) Determine the income earned in farming mustard greens in Anawai Village, Wua-Wua District, Kendari City, and (2) The attitude of women farmers in in farming mustard greens in Anawai Village, Wua-Wua District. Kendari City. This research was conducted in Anawai Village, Wua-Wua District, Kendari City, and was carried out from September to November 2021 with a total of 20 samples that selected through census. The data was analyzed using descriptive descriptive method that was processed using the income of women farmers, and processed using the bloom taxonomy percentage formula to determine the attitudes of women farmers. The results showed that (1) The income earned by women farmers in farming mustard greens in Anawai Village, Wua-wua District, Kendari City, is Rp 2.372.000/farming season with an average income of Rp 118.600, and was obtained from total revenue in the form of sales of mustard greens production, and total expenses in the form of fixed costs and variable costs. (2) The attitude of women farmers in farming mustard greens in Anawai Village, Wua-Wua District, Kendari City, which is more dominant is at the organizational level (A4) with a total of 12 respondents with a percentage of 60%.